2, 4-D Past, Present, and Future: A Review. (June 2016) - Peterson, Mark A.; McMaster, Steve A.; Riechers, Dean E.; Skelton, Josh; Stahlman, Phillip W.
Abstract : Since its discovery and initial commercialization in the 1940s, 2, 4-D has been an important tool for weed control in a wide variety of crop and noncrop uses. Work studying its chemistry, physiology, mode of action, toxicology, environmental behavior, and efficacy has not only helped elucidate the characteristics of 2, 4-D but also provided basic methods that have been used to investigate the properties of hundreds of herbicides that followed it. Much of the information published by researchers over 60 yr ago is still pertinent to understanding the performance of 2, 4-D today. Further, new studies continue to be published, especially regarding the mechanisms of 2, 4-D action at the molecular level. New uses for 2, 4-D, sometimes enabled by biotechnology, continue to be developed. This review strives to provide an overall understanding of 2, 4-D activity in plants, plant sensitivity to 2, 4-D, toxicological impacts, and current and future uses.